Electrochemical Behavior of Duloxetine Hydrochloride at Au and GC Solid Electrodes: Its Quantitative Determination and Degradation. Issue 7 (1st July 2022) - Lović, Jelena; Bogdanović, Aleksandra; Tadić, Vanja; Mijin, Dušan; Vuković, Dragan; Petrović, Slobodan; Ivić, Milka Avramov
Abstract : Duloxetine hydrochloride (DUL) is effective in treating depression, and was examined for electroanalytical purposes. The DUL standard was investigated by cyclic voltammetry (CV) and determined using differential pulse voltammetry (DPV) via its electro-oxidation at the Au electrode in 0.05 M NaHCO3 . DPV showed a linear dependency of the anodic peak currents vs DUL standard concentrations in the range from 0.1 to 3.33 μ g ml −1 with the values of the limit of detection (LOD) and the limit of quantification (LOQ): 0.133 and 0.667 μ g ml −1, respectively. Using the constructed and validated calibration curve, the values of unknown DUL concentrations in both Taita ® tablets and in human serum spiked with the standard were determined. The number of protons and electrons transferred was calculated and possible reaction mechanisms taking place on the surface of both electrodes were proposed. The Au electrode exhibited a better sensitivity and a wider range of current vs concentration linear dependency for DUL quantitative determination than the GC electrode. The study of DUL degradation showed that at the Au and GC electrodes, after 4.5 h of potential cycling, degradation occurs, giving formaldehyde as a product, which was confirmed by high performance liquid chromatography (HPLC).